An approach using highly sensitive carbon nanotube adhesive films for crack growth detection under flexural load in composite structures. (15th September 2019) - Sánchez-Romate, Xoan F.; Moriche, Rocío; Jiménez-Suárez, Alberto; Sánchez, María; Güemes, Alfredo; Ureña, Alejandro
Abstract: Sensing capabilities of carbon nanotube (CNT) doped adhesive films under bending conditions were investigated. Standard Mode-II coupons and skin-stringer sub-elements were manufactured while their electrical resistance was monitored. Mode-II energy fracture was improved when adding CNTs in comparison to neat adhesive joints due to their toughening effect. Electrical monitoring showed a stable increase of the electrical resistance with crack length with lower sensitivity than Mode-I testing due to a lower crack opening effect. A good agreement was observed by comparing to theoretical estimations, indicating a uniform adhesive distribution inside the joint, confirmed by SEM analysis. Monitoring tests on skin-stringer sub-elements subjected to bending load showed a similar behavior but some sharp increases were observed, especially in the last stages of the test, due to a less uniform adhesive distribution in the central region. Therefore, the proposed technique shows a high potential and applicability for Structural Health Monitoring of composite structures.